An Exploration of Observed Practices in Bilingual Education and the Bilingual Experience - Monaghan, Siobhán (Trinity College (Dublin, Ireland). School of Education, 2020)
This dissertation comprises of a literature review on the common practices for teaching English Language Learners (also known as Culturally and Linguistically Diverse learners) in bilingual education. This dissertation also comprises of a brief quantitative research study that takes what literature deems as common practice in bilingual education and uses it to survey a small participant pool of former bilingual students and their parents. This survey seeks to reveal if whether or not common practice in bilingual education was observed in the experiences of the participants and their parents. Keywords: Bilingualism, Bilingual Education, Quantitative Research
Keywords: Education; Language Studies